Microplastics and nanoplastics in the brain: a review of the neurodevelopmental risks - Antonio Ragusa; Vassilios Fanos (Journal of Pediatric and Neonatal Individualized Medicine)
Background: Microplastics (MPs, < 5 mm) and nanoplastics (NPs, 1-1,000 nm) – collectively referred to as MNPs – have become pervasive environmental contaminants. Their potential accumulation in the human body, particularly in the brain, has raised significant health concerns.